Perbaikan Sifat Kimia Tanah dan Pertumbuhan Kelapa Sawit Rakyat TM-1 Dengan Pemberian Kombinasi Pupuk Anorganik-Organik dan Asystasia gangetica (L.) T. Anderson Sebagai Tanaman Penutup Tanah - Yenni Asbur; Rizkon Jadida Pulungan; Yayuk Purwaningrum; Murni Sari Rahayu; Chairani Siregar; Dedi Kusbiantoro; Khairunnisyah Khairunnisyah (Pusat Penelitian Kelapa Sawit, 2023)
Currently, the area of ​​smallholder oil palm plantations in Indonesia reaches 41.44% and is wider than state-owned oil palm plantations which are only 3.87%. However, the role of smallholder oil palm plantations is still not optimal due to low land productivity and yields, so technical culture management is needed that can maintain land productivity and oil palm yields in a sustainable manner through the provision of a combination of inorganic-organic fertilizers and TPT planting. The purpose of this study was to determine the effect of inorganic-organic fertilizers and A. gangetica as TPT in improving soil chemical properties and growth of oil palm TM-1. The study used a factorial randomized design with three replications with two treatment factors, namely a combination of inorganic-organic fertilizers and TPT. The results showed that the interaction of P4T1 (100% inorganic 100%-organic fertilizer combination + TPT) and P3T1 (100% inorganic 100%-organic fertilizer combination + TPT) was able to improve soil chemical properties and growth of oil palm TM-1. Meanwhile, independently the combination treatment of 100% organic 100% inorganic fertilizer and TPT A. gangetica produced the most female flowers and the lowest male flowers.